Observations of semidiurnal internal tides on the Patagonian Shelf - Zhang, Tianyi (2018)
The Patagonian Shelf in the western South Atlantic is known for strong semidiurnal tides and intense seasonal stratification. Both observations and models reveal substantial cross-isobath tidal energy fluxes at the shelf break between 44 and 41°S. These conditions are potentially favorable for internal wave generation, but global tidal models do not show significant baroclinic energy radiation from this region. A possible explanation for the lack of offshore radiation is explored through analyzing the data from two moorings deployed along the Patagonian shelf break. At both mooring sites, the velocity spectra reveal strong baroclinic oscillations at the semidiurnal frequency with a vertical structure resembling the first mode. Unlike barotropic tides with strong cross-isobath polarization, the baroclinic tidal ellipses are less polarized. Internal tide propagation is delineated by estimating a proxy for the baroclinic energy flux, which is the product of band-passed baroclinic velocity near the bottom and temperature at mid-depth. The proxy vectors show that internal tide propagation is highly sensitive to the strength of the Malvinas Current propagating northward over the continental slope. When the mean current becomes stronger, the proxy vectors turn southward, pointing upstream of the Malvinas Current direction. It is concluded that the presence of an energetic western boundary current reduces the offshore radiation of internal tides, likely due to the wave refraction on the mean current.